2012
DOI: 10.1016/j.brainres.2012.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mct1 by cAMP-dependent internalization in rat brain endothelial cells

Abstract: In the cerebrovascular endothelium, monocarboxylic acid transporter 1 (Mct1) controls blood-brain transport of short chain monocarboxylic and keto acids, including pyruvate and lactate, to support brain energy metabolism. Mct1 function is acutely decreased in rat brain cerebrovascular endothelial cells by β-adrenergic signaling through cyclic adenosine monophosphate (cAMP); however, the mechanism for this acute reduction in transport capacity is unknown. In this report, we demonstrate that cAMP induces the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 58 publications
4
31
0
Order By: Relevance
“…The effect is posttranslational (Figure 1d) and as such may involve a reduced turnover rate of both proteins known to be subject to endosome-dependent recycling. 29,30 These responses to low glucose further explain the metastatic stimulation that can be associated with the use of anti-angiogenic drugs 31 and the higher expression of MCT1 in metastatic lesions compared to primary tumors in patients. 32 Conversely, increased MCT1 expression promotes the anticancer activity of 3-bromopyruvate, 33 an alkylating agent strictly dependent on MCT1 for its uptake, 34 thus offering a new rationale for combination therapy with anti-angiogenic or antivascular drugs.…”
Section: Discussionmentioning
confidence: 92%
“…The effect is posttranslational (Figure 1d) and as such may involve a reduced turnover rate of both proteins known to be subject to endosome-dependent recycling. 29,30 These responses to low glucose further explain the metastatic stimulation that can be associated with the use of anti-angiogenic drugs 31 and the higher expression of MCT1 in metastatic lesions compared to primary tumors in patients. 32 Conversely, increased MCT1 expression promotes the anticancer activity of 3-bromopyruvate, 33 an alkylating agent strictly dependent on MCT1 for its uptake, 34 thus offering a new rationale for combination therapy with anti-angiogenic or antivascular drugs.…”
Section: Discussionmentioning
confidence: 92%
“…The Canonical Wnt/␤-Catenin Pathway Increased Expression of MCT1 on the Plasma Membrane of RBE4 Cells-Our previous study revealed an endosomal/lysosomal trafficking pattern for MCT1 that was regulated by the cAMP signaling pathway (49). Furthermore, the MCT1 protein sequence contains several peptide motifs that are highly involved in the endosomal/lysosomal sorting process, such as the dileucine (LI) motif, YXX motif, and acidic clusters (52,55,56) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Culture-RBE4 cells were cultured as described previously (48,49) in a humidified incubator at 37°C with 5% CO 2 . All experiments were conducted when the cells reached 80 -90% confluence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another process, adsorptive endocytosis recycles bound/internalized blood products back into the vessel lumen, which occurs when plasma proteins like heparin, albumin, immunoglobulin G, or wheat germ agglutinin (WGA) interact with the apical plasma membrane and bind to the cell surface or enter the cell within an endosome [163,[171][172][173]. A series of outcomes may arise from adsorptive endocytosis: (1) these endosomes may be recycled back to the apical plasma membrane, where their contents are released back into the circulation; (2) the internalized endosome may fuse with a lysosome, where the endosomal contents will be degraded preventing any unwanted, harmful blood-borne products from contacting the brain parenchyma; (3) adsorptive endocytosis can lead to delivery of materials at the basal plasma membrane and the release of endosomal contents into the CNS; and (4) endosomes may invaginate forming multivesicular bodies which then release EVs (exosomes) containing cell contents into the extracellular space [163,172,174]. Of course, the first two of these endpoints present challenges to delivering therapeutic products to the brain; however, and importantly from the standpoint of a viral vector delivery mechanism, the process of adsorptive endocytosis could offer favorable outcomes considering that this may be the primary method for which blood-borne (a.k.a.…”
Section: Blood-brain Barriermentioning
confidence: 99%